The importance of preoperative diagnosis of blister aneurysms. Issue 9 (September 2015) - Russin, Jonathan J.; Kramer, Daniel R.; Thomas, Debi; Hasson, Denise; Liu, Charles Y.; Amar, Arun P.; Mack, William J.; Giannotta, Steven L.
Abstract: We describe a series of 14 surgical blister aneurysm (BA) patients and compare outcomes in those with known cerebral BA to those lacking preoperative BA diagnosis/recognition. BA are broad, fragile, pathologic dilatations of the intracranial arteries. They have a low prevalence but are associated with substantially higher surgical morbidity and mortality rates than saccular aneurysms. A confirmed, preoperative BA diagnosis can alter operative management and technique. We performed a retrospective review of prospectively collected data on aneurysm patients undergoing surgery at a major academic institution. All patients from 1990 to 2011 with a postoperative BA diagnosis were included. Chart reviews were performed to identify patients with preoperative BA diagnoses and collect descriptive data. We identified 14 patients, 12 of whom presented with subarachnoid hemorrhage. The age of the cohort (mean ± standard deviation: 41.8 ± 13.9 years) was lower than that generally reported for saccular aneurysm populations. Preoperatively diagnosed BA had an intraoperative rupture (IOR) rate of 28.6% (2/7) compared to a 57.1% (4/7) rate in the undiagnosed patients. The mortality rate in the preoperatively diagnosed cohort was 14.3% (1/7) while that of the undiagnosed group was 42.8% (3/7). BA remain a diagnostic and treatment challenge with morbidity and mortality rates exceeding those of saccular aneurysms. Preoperative BA diagnosis may decrease IOR and mortality rates and improve patient outcomes.